Technologies for prenatal diagnosis - Mantegazza, Franco (Medicina e Morale, 2024)
The possibility of examining the foetus during the first months of gestation in order to diagnose any structural abnormalities is a recent acquisition in modern obstetrics. This has been made possible by the introduction of the use of ultrasound for diagnostic purposes, and the refinement of the technique of taking amniotic fluid (amniocentesis).